(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In this article, it will be attempt to set up an analytical framework about the reactions to the development of the rail road system in San Luis Potosi in 1888, taking into count the legitimacy strategies used by the governing regime. The strategies were based on modernity and positivism. Firstly, we will tackle the key concepts in order to understand the events involved in the development of the rail road system in San Luis Potosi in 1888. Secondly, it will be attempt to put into practice those key concepts in order to explain the specific situation like the patriotic demonstration which took part during the grand opening of the Mexican rail road system on November 2nd , 1888, according to our research , it projected and legitimated the philosophy of the governing regime.